Peranan metode feldenkrais sebagai alternatif penatalaksanaan nyeri kronis - Ida Ayu Sri Wijayanti (E-Jurnal Medika Udayana, 2018)
Chronic pain is a multidimensional problem and conditions are common in society, complex and challenging. It is important to understand the biological, social, physical and psychological context to provide an effective management. The management of chronic pain focuses on the rehabilitation program and the quality of life of the sufferers, because chronic pain usually associated with anxiety, depression and psychosocial disorders that accompany persistent physical pain. The alternative therapy in the management of chronic pain is the Feldenkrais method. The Feldenkrais method is an integrated approach technique to provide learning and enhancement of functionality to individuals based on their abilities over the life span and aims to improve human ability to regulate their own behavior. This method includes simple motion exercises and awareness training through movement patterns as well as thinking, sensing, which can improve mentally positive and help reduce chronic pain complaints. Keyword: Feldenkrais Method, Chronic pain, Alternative Medicine